BAGAIMANA EFEKTIVITAS SUKUK DI TENGAH PANDEMI COVID-19? - Jubaidi, Jubaidi; Anitra, Vera (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The uncertain economic conditions during the Covid-19 pandemic caused investors in the capital market to have to think again about investing their funds when buying products on the capital market. This study aims to assess the effect of the Covid-19 pandemic on the level of demand for corporate sukuk in Indonesia. This study used a quantitative method with data in the form of time series and data collection techniques using the documentation method and analyzed by paired t test, Wilcoxon signed-ranks test, and sign test. The results show that corporate sukuk are still the most appropriate choice for the public to invest in the Islamic capital market as evidenced by the data on the development of sukuk from 2016 to 2021 which continues to increase, even though the increase during the pandemic was not as high as before the pandemic occurred.